Lyme disease presenting with facial palsy and myocarditis mimicking myocardial infarction - Julieta Gilson; Koroush Khalighi; Farhad Elmi; Mahesh Krishnamurthy; Amirsina Talebian; Rubinder S. Toor (Greater Baltimore Medical Center, 2017)
A 45-year-old woman presented with a sudden episode of typical chest pain, radiating to her neck. The patient denied premature coronary artery disease in the family. Initial EKG showed normal sinus rhythm with a 1 mm ST-elevation involving lead II and lead aVF and a 1 mm ST-depression in lead V1 with associated T-wave inversion. Initial Troponin I (normal <0.4 ng/mL) and CK-MB (normal <7.7 ng/mL) were elevated at 7.82 ng/mL and 55.2 ng/mL, respectively. Six hours later, Troponin I increased to 13.44 ng/mL and CK-MB to 75.7 ng/mL. The patient underwent cardiac catheterization which did not show any significant obstructive coronary artery disease. Two days later the patient developed right-sided facial palsy. Diagnosis of Lyme disease was confirmed by ELISA with positive IgM and IgG antibodies. Treatment with intravenous ceftriaxone and oral steroids was started. Eventually resolution of symptoms and, normalization of cardiac markers and EKG changes, were achieved. This is a rare case of Lyme myocarditis associated with markedly elevated Troponin I, normal left ventricle function, and an absence of conduction abnormalities. To the best of our knowledge, Lyme myocarditis mimicking acute coronary syndrome with such high levels of Troponin I and neurologic compromise has not been previously described. Lyme myocarditis may be a challenging diagnosis in endemic areas especially in patients with coronary artery disease risk factors, presenting with typical chest pain, EKG changes and positive cardiac biomarkers. Therefore, it should be considered a differential diagnosis in patients presenting with clinical symptoms suggestive of acute coronary syndrome. Abbreviations AV: Atrioventricular; CK-MB: Creatinine Kinase-MB; EKG: Electrocardiogram; ELISA: Enzyme-Linked Immunosorbent Assay; IgG: Immunoglobulin G; IgM: Immunoglobulin M